Contrasting dispersal histories of broad‐ and fine‐leaved temperate Loliinae grasses: range expansion, founder events, and the roles of distance and barriers. (19th April 2017) - Minaya, Miguel; Hackel, Jan; Namaganda, Mary; Brochmann, Christian; Vorontsova, Maria S.; Besnard, Guillaume; Catalán, Pilar
Abstract: Aim: Successful colonization after long‐distance dispersal (LDD) depends on the availability of suitable habitats and competitive ability. In this study, we address the hypothesis that two widely distributed sister grass lineages (broad‐ and fine‐leaved Loliinae; hereafter BL and FL) that differ in their habitat requirements and competitive ability also differ in their biogeographic history, with particular reference to LDD. Location: Global. Methods: We reconstructed a comprehensive phylogeny of Loliinae, based on nuclear and plastid markers and estimated divergence times using fossil calibrations. Biogeographical events were estimated using analysis of range evolution, comparing different models. Numbers and rates of dispersals were estimated for BL and FL using stochastic mapping with best‐performing and baseline biogeographical models, and examined for correlation with distance, disjunction type, and phenotypic syndrome. Results: The most recent common ancestor of Loliinae likely split at the Oligocene‐Miocene transition (22.50 ± 3.95 Ma), pre‐dating previous estimates, whereas the ancestors of the BL and FL Loliinae likely began to diversify in the Early Miocene (18.91 ± 4.15 and 17.50 ± 3.50 Ma, respectively). A model of range evolution integrating founder events and scaling of dispersal by shortest distance between areas performed best amongst a set of alternative models and recovered a mean of 83 dispersal events in Loliinae. Overall dispersal rates were significantly higher in BL than in FL. Per‐route dispersal rates showed a significant negative exponential relationship to shortest distance but were not affected by phenotypic syndrome or disjunction type. Main conclusions: Loliinae originated in the Northern Hemisphere and evolved through recurrent LDDs. Higher competitive ability, potentially related to the broad‐leaved syndrome (i.e. tall strong‐rhizomatous plants, long‐living individuals, occupancy of more stable habitats), may explain higher observed dispersal rates in BL compared with FL Loliinae. However, the dominant factor impacting dispersal in both BL and FL Loliinae is the distance between suitable areas.